Анализа укорељености нивоа цитокина и подгрупа Т лимфоцита периферне крви код системске васкуларне запаљенске болести: Ниво цитокина и подгрупе Т лимфоцита у периферној крви код системске васкуларне упалне болести - Lin, Zhonghan; Dong, Xuanyang; Chen, Junye; Li, Biao (Journal of Medical Biochemistry, 2025)
Objective: To measure the levels of T-cell subsets and cytokines in the peripheral blood of patients with systemic vascular inflammatory disease and to analyze the influence of different clinical characteristics of systemic vascular inflammatory disease patients on the levels of T-cell subsets and cytokines in the peripheral blood.Methods: The case group consisted of 80 systemic vascular inflammatory disease patients who were diagnosed and treated at our hospital between January 2021 and December 2024. Forty healthy volunteers were selected from our hospital's health assessment center to form the control group. The expression of helper T-cell (Th)1, Th17 and regulatory T-cell (Treg) subsets in the peripheral circulation was determined via flow cytometry. The levels of the cytokines interleukin and interferon-γ (IFN-γ) in the serum were measured via enzyme-linked immunosorbent assay (ELISA). levels of tumor necrosis factor-α (TNF-α), IL-4, IL-10, IL-17, and IL-6.Results: Compared with those in the control group, the expression levels of total T lymphoid subsets and CD8+ T and Th1 cells in systemic vascular inflammatory disease patients were significantly greater, and there was no statistically significant difference in Th, Th17, or Treg cell expression between the groups (P>0.05). However, there were statistically significant differences between the two groups [68.75 (54.23, 80.32)] and [72.10 (62.23, 86.45)], [23.44 (12.89, 33.76)] and [31.46 (20.13, 45.26)], [10.67 (8.23, 12.35)] and [10.26, 17.96 [25.39)], Z = -3.13, -4.54, -3.97 (all P values
Keywords: Системска васкуларна упална болест; Клиничке карактеристике; Подскупови Т лимфоцита; Ниво цитокина